A Dual Methodology for Case Studies: Synergistic Use of a Longitudinal Single Site with Replicated Multiple Sites - Leonard-Barton, Dorothy (Organization Science, 1990)
This paper describes a case study methodology that combines a real-time longitudinal (three-year) study with nine retrospective case studies about the same phenomenon. These two kinds of case studies offer opportunities for complementary and synergistic data gathering and analysis. That is, specific strengths in each method compensate for some particular weakness in the other. For instance, the retrospective studies offer the opportunity to identify patterns indicative of dynamic processes and the longitudinal study provides a close-up view of those patterns as they evolve over time. The combination of the two types of case studies also enhances three kinds of validity: construct, internal and external. The author also discusses problems with and shortcomings of this dual methodology and suggests the circumstances for which the methodology is especially appropriate.